Paying Them to Hate US: The Effect of U.S. Military Aid on Anti-American Terrorism, 1968-2014 - Daniel Meierrieks; Tim Krieger; Eugen Dimant (ZBW - Leibniz Information Centre for Economics, 2020)
Does U.S. military aid make the United States safer? To answer this question, we collect data for 173 countries between 1968 and 2014. Exploiting quasi-random variation in the global patterns of U.S. military aid, we provide causal estimates of U.S. military aid on anti-American terrorism. We find that higher levels of military aid lead to an increased likelihood of the recipient country producing anti-American terrorism. This finding also holds when subjected to a battery of robustness checks (e.g., alternative instrumental variables, sub-sample analyses, examination of heterogeneous effects, placebo tests). For our preferred specification, at the sample mean doubling U.S. military aid increases the risk of anti-American terrorism by 4.4 percentage points, which in turn is approximately 30% of the sample mean. Examining potential transmission channels, we find that more U.S. military aid leads to more corruption and exclusionary policies in recipient countries. Consistent with a theoretical argument developed in this paper, these results indicate that the inflow of military aid induces rent-seeking behavior, which in turn encourages terrorism by groups that suffer from reduced economic and political participation as a consequence of rent-seeking. These groups in particular direct their dissatisfaction against the United States as the perceived linchpin of an unfavorable status quo in the recipient country.
Keywords: D74; F35; 330; U.S. military aid; anti-American terrorism; transnational terrorism; instrumental variable estimation